2018
DOI: 10.4196/kjpp.2018.22.3.257
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cinnamic acid on memory deficits and brain oxidative stress in streptozotocin-induced diabetic mice

Abstract: The present study aimed to evaluate the cinnamic acid effect on memory impairment, oxidative stress, and cholinergic dysfunction in streptozotocin (STZ)-induced diabetic model in mice. In this experimental study, 48 male Naval Medical Research Institute (NMRI) mice (30–35 g) were chosen and were randomly divided into six groups: control, cinnamic acid (20 mg/kg day, i.p. ), diabetic, and cinnamic acid-treated diabetic (10, 20 and 40 mg/kg day, i.p. ). Memory was impaired by administering an intraperitoneal STZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 67 publications
2
29
1
Order By: Relevance
“…Further, diabetic mice of both genotypes (WT and KO) showed decrease in movement velocity and the number of arm entries at 8 weeks post-MLDS injection, which might be associated with diabetes-induced motor impairments. In line with our findings, several studies have shown a reduction in the number of total arm entries of diabetic mice compared with non-diabetic controls (5961). Likewise, another study has found a marked reduction in speed and traveling distance of diabetic mice, indicating impairment of exploratory behavior and motor activity (62).…”
Section: Resultssupporting
confidence: 93%
“…Further, diabetic mice of both genotypes (WT and KO) showed decrease in movement velocity and the number of arm entries at 8 weeks post-MLDS injection, which might be associated with diabetes-induced motor impairments. In line with our findings, several studies have shown a reduction in the number of total arm entries of diabetic mice compared with non-diabetic controls (5961). Likewise, another study has found a marked reduction in speed and traveling distance of diabetic mice, indicating impairment of exploratory behavior and motor activity (62).…”
Section: Resultssupporting
confidence: 93%
“…Concerning the direct effects of phenolic acids on the central nervous system, it has been demonstrated that hydroxycinnamic acids and their esters may exert beneficial effects toward cognitive functions by improving neuronal cell antioxidant activity against oxidative stress [ 47 , 48 ], through various signaling pathways including Nrf2/HO-1 pathway [ 49 ]. Moreover, hydroxycinnamic acids have been shown to rescue memory deficits in animal models of diabetes induced by streptozotocin through the reduction of oxidative stress and the positive modulation of the PI3-kinase pathway [ 50 , 51 ]. Among hydroxybenzoic acids, gallic acid has been shown to reverse impaired learning and memory in a rodent model of Alzheimer’s disease through simultaneous elevation of α-secretase and reduction of β-secretase activity and, most importantly, activation of metalloproteinase domain-containing protein 10 [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the UCLouvain Ethical Committee (Brussels, Belgium; permit number: 2015/UCL/MD/07) and was conducted in accordance with the Practice Guidelines for Laboratory Animals of Belgium. NMRI mice are a well-known mice model for streptozotocin-induced T1D [1618]. Moreover, the multiple low-dose STZ-induced diabetes mice model is a model widely used to demonstrate the effect of drug treatment or knockdown in type 1 diabetic mice.…”
Section: Methodsmentioning
confidence: 99%